PENGARUH MODEL PEMBELAJARAN ROUND TABLE BERBANTUAN MEDIA GAMBAR SERI TERHADAP KETERAMPILAN KARANGAN NARASI SISWA KELAS IV SDN 1 TERONG TAWAH TAHUN PELAJARAN 2020/2021 (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
This study aims to determine whether there is an effect of the round table learning model assisted by picture series media on the narrative essay writing skills of fourth grade students of SDN 1 Terong Tawah in the 2020/2021 academic year. This type of research is experimental research (Quasi Experiment). This research design uses Repeated Treatment. The population in this study were fourth grade students at SDN 1 Terong Tawah. The sampling technique used is purposive sampling, the sample is class IVB SDN 1 Terong Tawah. The data collection methods used were observation and written tests, writing narrative essays, and documentation. The data from the results of writing narrative essays were in the form of pretest, posttest 1, posttest 2, and posttest 3. The data obtained were then analyzed using the ANOVA repated measure formula to determine whether there was an effect of the round table learning model assisted by serial image media on students' narrative essay writing skills. Based on the results of the ANOVA repeated measure test, a significance number of 0.000 was obtained, which was smaller than 0.05. This shows that Ha is accepted and H0 is rejected. So it can be concluded that there is an effect of the round table learning model assisted by serial picture media on the narrative essay writing skills of fourth grade students of SDN 1 Terong Tawah in the 2020/2021 academic year.
Keywords: Model pembelajaran round table; media gambar seri; keterampilan menulis; karangan narasi